2010
DOI: 10.1111/j.1540-8175.2009.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Regurgitation after Orthotopic Heart Transplantation

Abstract: There appears to be no difference between the TR severity and TR velocity at early and late time points regardless of anastomotic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The meta-analysis results of all the significant studies are shown in Table 2-9. [2,7,8,10,11,[13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35]37,38,40,41,44] Park et al [21] 2005 RS South Korea 25 13 Asian Cardiovasc Thorac Ann Aziz et al [7] 1999 PNRCT UK 96 105 J Thorac Cardivasc Surg Solomon et al [22] 2004 RS New Zealand 37 38 Heart Lung Circ Sarsam et al [11] 1993 PRCT UK 20 20 J Card Surg el Gamel et al [13] 1995 PRCT UK 40 35 J Thorac Cardivasc Surg Traversi et al [23] 1998 NRCT Italy 22 27 J Heart Lung Transplant Kalra et al [43] 2010 RS USA 56 57 Echocardiography Sievers et al [10] 1994 PRCT Germany 8 10 J Thorac Cardivasc Surg Meyer et al [17] 2005 RS Canada 41 34 Can J Cardiol Leyh et al [14] 1995 PRCT Germany 15 12 Ann Thorac Surg Grant et al [18] 1995 PS UK 31 35 Br Heart...…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis results of all the significant studies are shown in Table 2-9. [2,7,8,10,11,[13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35]37,38,40,41,44] Park et al [21] 2005 RS South Korea 25 13 Asian Cardiovasc Thorac Ann Aziz et al [7] 1999 PNRCT UK 96 105 J Thorac Cardivasc Surg Solomon et al [22] 2004 RS New Zealand 37 38 Heart Lung Circ Sarsam et al [11] 1993 PRCT UK 20 20 J Card Surg el Gamel et al [13] 1995 PRCT UK 40 35 J Thorac Cardivasc Surg Traversi et al [23] 1998 NRCT Italy 22 27 J Heart Lung Transplant Kalra et al [43] 2010 RS USA 56 57 Echocardiography Sievers et al [10] 1994 PRCT Germany 8 10 J Thorac Cardivasc Surg Meyer et al [17] 2005 RS Canada 41 34 Can J Cardiol Leyh et al [14] 1995 PRCT Germany 15 12 Ann Thorac Surg Grant et al [18] 1995 PS UK 31 35 Br Heart...…”
Section: Resultsmentioning
confidence: 99%
“…Kim and colleagues found that post-transplant tricuspid regurgitation did not affect long-term survival, and it was not related to the anastomosis technique, but the donor age was significantly associated with the occurrence of postoperative tricuspid regurgitation [ 5 ]. In an echocardiographic study comparing bi-caval versus atrial anastomosis technique, no effect of the technique on tricuspid regurgitation was found [ 6 ]. Several studies found that bi-caval technique decreased the post-transplant tricuspid regurgitation [ 7 – 10 ], and all patients in our study had bi-caval anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…3,17 The factors responsible for the development of TI following HTx widely reported in the literature are age, ischemic time, time after operation, steroid use, number of rejections, pulmonary hypertension, operative technique, donor/recipient size miss match, coronary artery vasculopathy, and the use of dialysis. 7,12,[18][19][20][21][22][23] Incidence of TI was retrospectively examined in 857 of 1515 patients. Thirty-eight percent, or n ¼ 327, of patients had no TI, 43% (n ¼ 369) TI I, 13% (n ¼ 109) TI 2, 5% (n ¼ 42) TI 3, and 1% (n ¼ 10) TI 4.…”
Section: Discussionmentioning
confidence: 99%